Some Problems on the Sectoral Structure, GDP Growth and Sustainability of Vietnam - Trinh, Bui; Quoc, Bui (Journal of Reviews on Global Economics, 2017)
The Vietnam development has been enjoying a great deal of rapid economic growth in the last decades, which thank to the opening of market-oriented economy system. However, the economic growth is slowly recent years and the increase of environmental issues. The reason for this situation is that misallocation of resource, the sectoral development policies as well as the development orientation of the government. In order to find the solution, this research applies the input output model to analysis the sectoral structure and economic growth as well as the sustainability of economic growth and the effect of economics on the environment. Then, this research recommends the better sectoral structure for Vietnam in order to allocate resources efficiently and forward to the sustainable development. The purpose of this study was to point out the instability of Vietnam, not only for the environment but also for the whole economy. Research shows that VN is not only the face of environmental pollution, but also uncertainty about macroeconomic. It also pointed out the need to change the economic structure for economic development that the environment in a sustainable way. This research based on Leontief and Ghosh systems